Acute Effects of Post-Activation Potentiation on Explosive Strength Performance in Wrestling Athletes - Şeref Eroğlu, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Researching methods of improving athlete performance has always been a topical issue. When the studies conducted in this context are examined, many different applications and methods of improving sportive performance have been tested. Especially Post-Activation Potential (PAP) is a very popular subject, and the lack of consensus among researchers on how long the rest period will be after PAP application makes this subject worth investigating. Aim: The aim of this research is to determine the most appropriate resting time interval to produce the highest explosive power after the PAP protocol. Methods: The mean age of the participants group of the research was 19,31±1,21, their height was 170,31±3,42, their weight was 69,09±4,06 and their maximal squat one repetition performance (1-RM) was 86,36±5,60. In this research, measurements were completed on five separate days with 72 hour intervals. On the first measurement day, the athletes' height and weight measurements, 1-RM squat measurements, vertical jump performance measurements were taken and explosive strength levels were calculated using the Lewis formula. On the second measurement day, 5 repetitions were performed with 85% of the 1-RM squat and after 15 seconds of rest, the vertical jump performance test was measured. On the third measurement day, 5 repetitions of 1-RM squats with 85% were performed and after 3 minutes of rest, the vertical jump performance test was measured. On the fourth measurement day, 5 repetitions of 1-RM squat with 85% were performed and after a rest period of 6 minutes, the vertical jump performance test was measured. Finally, on the fifth measurement day, 5 repetitions of 1-RM squats with 85% were performed and after 9 minutes of rest, the vertical jump performance test was measured. After all measurements, explosive strength levels were calculated using Lewis formula. Passive rest was performed between the exercise and the measurement. Results: As a result of the findings of our research, it was determined that the 15-second rest time interval after the PAP protocol negatively affected the explosive strength performance level. In addition, there was no statistically significant difference between 3 min, 6 min and 9 min rest time intervals. Conclusion: It can be said that the most appropriate resting time is between 3-9 minutes in terms of increasing the explosive strength performance of wrestlers after the PAP protocol.